DIMENSI SOSIAL DALAM FILSAFAT MULLA SADRA - Supratman, Supratman (Universitas Hasanuddin, 2019)
Hikmah Muthaaliyah (Transcendent Wisdom) is the Philosophy of Mulla Sadra. The uniqueness of this philosophy is not only summarizing the various approaches that have been taken by previous philosophers - from Greece to the Muslim world (Middle East) - but also completes and adds new approaches in the form of irfan and also references to the Koran and the hadith of the Prophet Muhammad SAW .The completeness of the approach accompanied by an accurate understanding of the sources of Islamic teachings, this philosophy is called the most complete philosophy in terms of the scope of the discussion. Therefore, the discussion of social issues has a very strong position in the philosophy of Mulla Sadra.The social issues can be explained by elaborating the theory of the substance motion (Al-Harakah Al-Jauwhariyyah) and the four intellectual journeys (Al-Asfar Al-Arbah Al-Aqli).